173k views
1 vote
The parent function f(x) = x3 is translated to form g(x), as shown on the graph. The translated function can be written in the form

g(x) = (x – h)3 + k.

The parent function f(x) = x3 is translated to form g(x), as shown on the graph. The-example-1
The parent function f(x) = x3 is translated to form g(x), as shown on the graph. The-example-1
The parent function f(x) = x3 is translated to form g(x), as shown on the graph. The-example-2
User Aphax
by
5.2k points

2 Answers

0 votes

Answer:

A

Explanation:

edge 2021

User Pevara
by
4.8k points
2 votes

Answer: First option

Explanation:

By definition, the horizontal shift depends on the value of h and the vertical shift depends on the value of k.


f(x)=(x-h)^3 indicates that the function if shifted to the right h units.


f(x)=(x+h)^3 indicates that the function if shifted to the left h units.


f(x)=f(x)-k indicates that the function if shifted down k units.


f(x)=f(x)+k indicates that the function if shifted up k units.

Then:

If h is positive, the graph will shift to the right.

If k is negative, the graph will shift down.

As you can see in the graph, the function is shifted 4 units to the right and 2 units down. Therefore g(x) has the form:


g(x)=(x-4)^3-2

Where:


h=4\\k=-2

User Roger Dodger
by
5.7k points